Growth-sector dependence of morphological, structural, and optical features in boron-doped HPHT diamond crystals - Strelchuk, V.V.; Nikolenko, A.S.; Lytvyn, P.M.; Ivakhnenko, S.O.; Kovalenko, T.V.; Danylenko, I.M.; Malyuta, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
Semiconducting boron-doped diamond single crystals of cubo-octahedral habit with prevalent development of octahedron {111} faces, and insignificant area of cube {001}, rhombo-dodecahedron {110}, and tetragon-trioctahedron {311} faces were obtained using solution-melt crystallization at high pressure 6.5 GPa and temperatures 1380…1420 °C. Using the Fe-Al solvent, which allows controlled incorporation of boron dopant between 2·10⁻⁴…10⁻² at.%, made it possible to vary the electro-physical properties of the crystals. Methods of micro-photogrammetry, atomic force microscopy, and micro-Raman spectroscopy were applied to reveal sectoral inhomogeneity of impurity composition and morphology of different crystal faces. The obtained crystals were shown to have high structural perfection and boron concentration ranging approximately from 1·10¹⁷ up to 7·10¹⁸ cm⁻³. An increase in boron concentration increases the area of {111} faces relatively to the total crystal area. Nanoscale morphological features like growth terraces, step-bunching, dendrite-like nanostructures, columnar substructures, and negative growth pyramids on different crystal faces are shown to reflect peculiarities of carbon dissolution at high pressures and temperatures. The changes in the crystals’ habit and surface morphology are discussed in relation to the inhomogeneous variation of thermodynamic conditions of crystal growth and dissolution at different boron concentrations. Леговані бором напівпровідникові монокристали алмазу кубооктаедричного габітусу з переважним розвитком граней октаедра {111} і незначною площею граней куба {001}, ромбододекаедра {110} і тетрагонтриоктаедра {311} було отримано методом розчин-розплавної кристалізації під високим тиском 6,5 ГПа і при температурах 1380…1420 °С. Використання розчинника Fe-Al, який дозволяє контролювати включення домішки бору у межах 2·10⁻⁴–10⁻² ат.%, дало можливість варіювати електрофізичні властивості кристалів. Методи мікрофотограмметрії, атомно-силової мікроскопії та мікрораманівської спектроскопії були застосовані для виявлення секторальної неоднорідності домішкового складу і морфології різних граней кристалів. Показано, що отримані кристали мають високу структурну досконалість і концентрацію бору від ~1·10¹⁷ до ~7·10¹⁸ см⁻³. Збільшення концентрації бору призводить до зростання площі граней {111} у порівнянні із загальною площею кристала. Показано, що нанорозмірні морфологічні особливості, такі як тераси росту, сходинки, дендритоподібні наноструктури, стовпчасті субструктури, негативні піраміди росту на різних гранях кристала відображають особливості процесів розчинення вуглецю при високому тиску і високих температурах. Зміни габітусу і морфології поверхні кристалів обговорюються у зв’язку з неоднорідною зміною термодинамічних умов росту і розчинення граней кристалів при різних концентраціях бору.